Does Technopark Play a Role in Local Economic Development? Case Study in Samosir Regency - Kuntias, Agisa; Novianti, Tanti; Fariyanti, Anna (Jurnal Ekonomi & Studi Pembangunan, 2022)
Local economic development is one of the development policies that is considered appropriate and strategic in the context of regional development in Indonesia by optimally utilizing local resources. In line with this concept, the Government of Samosir Regency established a technopark as a centre for innovation based on inland fishery resources to encourage local economic activities for the community. The purpose of this study is to examine the strategy of the local government of Samosir Regency in developing the local economy through technopark based on inland fishery resources. The analytical tool used by the Analytical Network Process (ANP) includes analysis of aspects of factors, problems, solutions, and alternative strategies. Based on the results of the ANP analysis, the collaboration factor is the most influencing factor in strategy development. Meanwhile, in the problem aspect, the problem of limited infrastructure, low public interest and weak commitment, are the main problems that need to be resolved, so that the solution aspect becomes a priority is building trust between stakeholders, allocation of financing for infrastructure and socialization of coaching programs to the community. The formulation of the main strategy for local economic development through the development of technoparks based on the results of the ANP analysis is to build multi-stakeholder synergy to support local economic development in Samosir Regency.